An Anthropology of Parking: Infrastructures of Automobility, Work, and Circulation. (28th October 2015) - Chelcea, Liviu; Iancu, Ioana
Abstract: While there is a growing anthropological literature on cars and infrastructures of automobility, it has failed so far to open up ethnographic analysis to nonmoving cars and the socialities that such immobile objects entail. Focusing on self‐appointed parking attendants in Bucharest – a growing presence since the early 2000s in many car traffic hotspots – we describe how informal parking allows a growing number of disenfranchised families and individuals to subsist. Parking, that is, the activity of helping drivers to find parking places, works in two related yet distinct ways: (1) it produces direct payments for forced, mostly unsolicited, parking services imposed on drivers who seek free parking spots; and (2) it maintains a social infrastructure composed of a highly provisional matrix of lateral connections, possibilities, and transactions that allows such self‐appointed parking attendants to circulate and live in a revanchist city. As self‐appointed parking attendants operate daily in many cities throughout the world, parking may be an excellent analytic window into work, poverty, and urban infrastructures.